Fatigue design of welded bicycle frames using a multiaxial criterion - Callens, A.; Bignonnet, A. (Procedia Engineering, 2012)
This paper describes the methodology developed by Decathlon, through its MKniX Engineering Center, to master the fatigue design of welded aluminium-alloy bicycle frame. The objective is to optimize the design prior to the standard testing by calculating the fatigue reliability of the bicycle frame. The fatigue assessment method is based on the Dang Van multiaxial fatigue criterion combined with a unique S-N design curve independent of the geometry of the welded structure and the loading mode. The design stress is defined through a linear elastic finite element analysis using a specific thin shell meshing method.